2019
DOI: 10.1016/j.neubiorev.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of hedonics in the Human Affectome

Abstract: Experiencing pleasure and displeasure is a fundamental part of life. Hedonics guide behavior, affect decision-making, induce learning, and much more. As the positive and negative valence of feelings, hedonics are core processes that accompany emotion, motivation, and bodily states. Here, the affective neuroscience of pleasure and displeasure that has largely focused on the investigation of reward and pain processing, is reviewed. We describe the neurobiological systems of hedonics and factors that modulate hed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 344 publications
(389 reference statements)
2
51
0
Order By: Relevance
“…The second example, “The Role of Hedonics in the Human Affectome” (Becker et al, 2019), presented a view of aesthetic pleasure from the point of view of mainstream neuroscience. It is a comprehensive review of literature pertaining to “Hedonics,” the core experience of pleasure and displeasure (Becker et al, 2019).…”
Section: The Problem With Artmentioning
confidence: 99%
“…The second example, “The Role of Hedonics in the Human Affectome” (Becker et al, 2019), presented a view of aesthetic pleasure from the point of view of mainstream neuroscience. It is a comprehensive review of literature pertaining to “Hedonics,” the core experience of pleasure and displeasure (Becker et al, 2019).…”
Section: The Problem With Artmentioning
confidence: 99%
“…Using these different approaches and definitions, several consistent emotion-related brain regions and neural networks [recently labeled the ''affectome'' (Becker et al, 2019)] have been identified. It must be emphasized at the outset, however, that even well-identified brain regions are generally very heterogeneous structures, in terms of both cell types and function.…”
Section: Neural Circuits and Emotionmentioning
confidence: 99%
“…This suggests that, while circuits may be similar, the efficacy of odors to modulate emotions and moods may differ. An odor that relieves a sad emotion following a favorite sports team's loss, may have much less impact on the major depressive FIGURE 2 | Schematic representation of the "affectome" (Becker et al, 2019), i.e., a network of mood/emotion-related brain regions. This schematic should be interpreted with the caveat that even well-identified, mood/emotion-related brain regions are generally very heterogeneous structures both structurally and functionally.…”
Section: Neural Circuits and Moodmentioning
confidence: 99%
“…Hedonic value relates to the information of enjoyment, satisfaction, and pleasure (Becker et al, 2019;Park & Nicolau, 2015;Yang et al, 2017). Perceived hedonic value of customers is more subjective than utilitarian and typically require entertainment, and playfulness also the entire experience of excitement, perceived freedom, acquired feelings such as social, cognitive, and emotional (Kazakevičiūtė & Banytė, 2013;Kim & Han, 2011).…”
Section: Hedonic Valuementioning
confidence: 99%